PENGARUH CAMPURAN PUPUK KANDANG DAN BATUAN FOSFAT ALAM TERHADAP PRODUKSI DAN SERAPAN N, P, K TANAMAN JAGUNG MANIS DI INCEPTISOL, SLEMAN - , HARIO TOMO, Dr. Ir. Sri Nuryani Hidayah Utami, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was done in the Education, Research and Agricultural Development Farm, Gadjah Mada University, Kalitirto, Berbah, Sleman, Yogyakarta. The aim of this research was to know influence goat manure and nature rock phosphate on N, P, K uptake and production of the sweet corn crops in Inceptisol, Sleman. The research method was the Randomized Complete Block Design (RCBD) with single treatment factor which three replications for each treatment. Details of the treatment are T0: without granule manure (control), T1:granule manure 2,5 ton/ha (mixed cattle manure and nature rock phosphate 5%), T2:granule manure 5ton/ha (mixed cattle manure and nature rock phosphate 5%), T3:granule manure 7,5ton/ha (mixed cattle manure and nature rock phosphate 5%). The analysis data of soil and plant growth parameters were analyzed by multiformity investigation (analysis of variance) and if the results showed significant differences using then Duncan Multiple Range Test (DMRT) at significant levels of 5 %. The result showed that granule then manure was not significant influe pH, macro nutrient (N P and K) soil and N, P, K uptake of sweet corn crops. The treatment of granule manure dosage had not increas crop productions (cob weight, cob diameters, cob lenght and weight of 100 seeds) was observed